Software EnfHA para a assistência de enfermagem às pessoas com hipertensão arterial na atenção primária à saúde - Oliveira, Gabriela (2024)
The research had as its general objective to build and validate a health technology based on the assumptions of Continuing Education in Health (EPS) and that directs nursing care to people with arterial hypertension (AH) treated in Primary Health Care (PHC). This study is based on participatory research and was conducted according to the conceptual model of Knowledge Translation into Action. The setting was the PHC and the participants were intentionally invited, according to their experience and performance, constituting the target audience, nurses working in the PHC, and expert judges in the areas of nursing and informatics. The stages of verification of existing knowledge with the target audience, synthesis of knowledge and construction of the knowledge tool were contemplated. Other stages were considered such as adaptation to the local context, evaluation of barriers and facilitators for the use of knowledge, selection and adaptation of interventions, all of this process occurred in a participatory manner with the management and nurses. Furthermore, the technology was validated with 15 nurses from the target audience and ten expert judges, considering the following software characteristics: functional suitability, usability, performance efficiency, compatibility and safety. To analyze the proportion of agreement between the responses, the Content Validity Index (CVI) was calculated. Ethical aspects were respected according to current resolutions. The product of the knowledge constructed was a software, called EnfHA, for which the needs and directions of the target audience were considered, in addition to the existing knowledge regarding nursing care for people with AH. The health technology was structured according to the stages of the Nursing Process (NP), consisting of the main screens for registering the nurse and team, a main menu with all the options that can be explored, among them the guide for the NP that includes explanations and directions for all the stages and the screen for performing the NP with the fillable fields for assessments and establishing nursing diagnoses and interventions. Furthermore, the technology makes it possible to obtain individual reports for monitoring and evaluation, and reports with collective information, for example, considering registered users with high cardiovascular risk. The software was validated with an overall CVI of 0.88 for the target audience, 0.99 for nursing judges and 0.95 for computer science judges. It was concluded that the construction of the knowledge tool occurred in a participatory manner with professionals and management, and that the technology was improved with validation. The results of this thesis have the potential to generate impact and be applied at local, regional and national levels, as they describe in a systematic way the steps for developing software to perform the NP, and can be used in care practice as a strategy for organization, agility and standardization of care, giving visibility to nursing activities in PHC aimed at people with hypertension.